Religious Conflict Management: A Study on the Ansor Youth Movement and Muhammadiyah in Lamongan, Indonesia - Huda, Sholihul; Al Amin, Mukayat; Muhsinin, Mahmud (Prodi Studi Agama-Agama, 2024)
Violence in the name of religion continues to sprout within Indonesian society. This article aims to describe the religious conflict resolution model of the NU Ansor Youth Movement and the Muhammadiyah Youth of the Paciran Lamongan Branch. This research employs a qualitative method with a sociological approach to religion, and data collection was conducted through interviews and the study of relevant literature. The findings of this study indicate that: 1) Both the NU Ansor Youth Movement and Muhammadiyah Youth reject violent models of preaching. 2) There is a difference in attitude towards perpetrators of violence, where the NU Ansor Youth Movement tends to adopt a non-accommodative firm stance, unequivocally rejecting and insisting that perpetrators of violence must be punished according to legal statutes, whereas Muhammadiyah Youth exhibits a firm-accommodative attitude, sternly condemning acts of violence but remaining willing to embrace and invite the perpetrators back to a tolerant and inclusive understanding. 3) The media of resolution employed include issuing advisory letters, press releases to the media, dialogues among community elements, conveying deradicalization insights through religious study sessions (Yasinan and Tahlilan), and the formation of Densus 99 Anti-Terror. 4) The conflict resolution model consists of two stages: long-term, aiming to build cadre awareness of the importance of a tolerant attitude and peaceful living through education, training, social and economic empowerment, ideological development, and the distribution of cadres to the public domain; and short-term, wherein preaching programs are executed sporadically and reactively at the time or after acts of violence to prevent the expansion and escalation of conflict.